Company Production Optimization Analysis Using Linear Programming Method (Case Study in Terang Alam Semesta MSMEs) - Firdausi Ahsan, Agung; Hidayat, Rachmad; Suswanto, Budyi (Universitas Trunojoyo Madura, 2023)
The development of the industrial world which is increasingly developing at this time will lead to high competition in the industrial world. So that the profits of each company also have an influence. New ideas are urgently needed to bring the business world in a more advanced direction so that it can keep up with increasingly fierce competition. Terang Alam Semesta is one of the MSMEs that operates in the Bag Manufacturing Sector. In this research, the Linear programming method is used as an operational research model in applied mathematics studies which is widely used in industry and business organizations and can be used in the process of obtaining solutions and solving production problems. From the results of research using POM for Windows software, it was found that Terang Alam Semesta would gain maximum profits if it could produce 15 Premium Leather Bags and 10 Semi-Leather Bags with a profit of IDR. 900,000 per day.